Recurrent bronchitis immunomodulation in children with vertebrobasilar arterial system syndrome - L. S. Ovcharenko; Т. V. Slutskaya; A. A. Vertehel; T. G. Andrienko; I. V. Samokhin; A. V. Kryazhev (Сучасні медичні технології)
Purpose of the study. To increase of recurrent bronchitis (RB) immunoprophylaxis effectiveness inchildrenaged 7 to 12 yearswiththevertebrobasilar arterial system syndrome (VBASS).